Digital marketing to increase sales of salted fish products in Muara Badak Ilir village, Kutai Kartanegara - Andi Nurhasanah; Muchamad Zainul Rohman (Universitas Muhammadiyah Magelang, 2021)
The development of information technology has grown rapidly and has an impact on society in supporting various large and small-scale business activities. Digital Marketing is one of the means to sell that can help increase product sales compared to conventional sales. This community service aims to provide training and assistance to members of the Rukun Nelayan Toko Lima, Muara Badak Ilir Village, Kutai Kartanegara Regency in marketing tembang and anchovy salted fFish products as regional superior products. This program was carried out through a Focus Group Discussion (FGD) to explore problems in product marketing as well as training and assistance in website management, design and marketing of tembang and anchovy salted fish products. The results of the program show that members of the Rukun Nelayan Toko Lima can skillfully manage marketing through digital marketing and website.